Hairline Restoration: Difference in Men and Woman—Length and Shape - Rodman, Regina; Sturm, Angela Kay (Facial Plastic Surgery, 2018)
Hair restoration has become increasingly popular in recent years with both men and women. New technologies such as follicular unit extraction and grafting have made it possible for patients to get a natural looking result with minimal downtime. Men usually experience hairline recession as a result of androgenic alopecia, while women most commonly experience thinning of the crown and vertex, with the preservation of the hairline. However, there is a growing population of women who wish to advance their hairline forward because of congenital high hairline, traction alopecia, or previous facial cosmetic surgery. There are several key differences between the female and male hairline. Understanding such differences and following certain guidelines will help the facial plastic surgeon to obtain beautiful and natural appearing results.
Keywords: hairline; hair transplant; hair restoration; follicular unit grafting; follicular unit extraction